Legal and philosophical approaches to memory and the right to be forgotten from a fundamental rights theory - Martínez López-Sáez, Mónica (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
Today’s world is characterized by digital memory as a categorical principle and oblivion only as the anomalous default. This calls into question the principle that human dignity is the foundation and highest value of any democratic and constitutional order, guaranteeing the right of every person to freely define their identity and life plan. Fundamental rights, arranged under the umbrella of human dignity and freedom, require a certain power of control, a sort of autonomous and informational self-determination, especially in the context of information and digital technologies. The European stance has been to regulate the so-called right to be forgotten as a personal data control guarantee given the automatic profiling, compilation and decontextualized presentation that NICTs generate and make universally-accessible in the online world. In response to the criticism that the European and Spanish regulation (2016 and 2018) have received, this article analyses, from a fundamental rights-based approach, the rationale behind the need for this mechanism to protect human dignity against the harmful resurrection that an instant click and a digital online memory produce.